Fungsi Seorang Agen Asuransi Syariah untuk Menumbuhkan Pengetahuan Masyarakat tentang Asuransi Syariah - Feri Prayogi; Nuri Aslami (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2022)
In this analysis, it tries to answer how the attitude of a customer acts on the existence of sharia insurance. Furthermore, how hard work, a sharia insurance agent to increase the awareness of the population. This research model is library analysis. The results of this analysis show that agents have the function of reaching out to information, maintaining the authority of sharia insurance, distributing solutions and interviewing customers who participate in sharia insurance. Keywords: customer actions, function of sharia insurance agents, channeling solutions